Metal and ligand control in di- and octa-nuclear cluster formation - Saalfrank, Rolf W.; Seitz, Verena; Heinemann, Frank Wilhelm; Göbel, Cornelia; Herbst, Imer Regine (Journal of the Chemical Society, Dalton Transactions, 2001)
Reaction of doubly negatively charged m-pyridinediyl spacered bis-bidentate ligands with iron(III) chloride in the presence of alkaline, alkaline earth, and rare earth metal cations (Mn+) yielded 2-iron cryptates M⊂[Fe2(L)3]n+. The mono-, di-, and tri-valent guest cations are endohedrally encapsulated in the cavity of the bicyclic dinuclear host. In contrast, the ligands reacted with Mn2+, Co2+, and Cd2+ (MII) cations as pentadentate tritopic chelators to give octanuclear complexes [MII8O 2(L)6]. Similarly, a topological equivalent pentadentate tritopic ligand L′ in the presence of Zn2+ cations afforded the octanuclear cluster [Zn8O2(L′)6]. However its reaction with iron(III) chloride and alkaline, alkaline earth, and rare earth metal cations did not lead to products of type M⊂[Fe 2(L)3]2+.
UnivIS-Import:2017-03-24:Pub.2001.forsch.sonder.sfb583.metala